Bazı Alifatik ve Aromatik Amin Metal Benzensülfonatların Sentezi, Spektroskopik ve Termik Özellikleri - Gürkan, Evrim Yılmaz (Ondokuz Mayıs Üniversitesi, Fen Bilimleri Enstitüsü, 2007)
Bu çalışmada, Mn(II), Co(II), Ni(II) ve Cu(II) geçiş metalleri ve imidazol (im), 1,10-fenantrolin (phen), 2,2'-bipridin (bpy), etilendiamin (en) ve akua ligantlarını içeren karışık ligantlı benzensülfonat kompleksleri ile benzensülfonik asidin (bsa) ligant olarak davrandığı [Mn(bsa)2(bpy)2]·H2O kompleksi sentezlendi. Bu komplekslerin bileşimleri elementel analiz ve iletkenlik ölçümleriyle; manyetik özellikleri manyetik duyarlık çalışmalarıyla; spektroskopik özellikleri IR ve UV-Vis teknikleriyle, termik davranışları ise eşzamanlı TG ve DTA teknikleri ile incelendi. [Mn(bsa)2(bpy)2]·H2O kompleksinin uygun tek kristali elde edilerek incelendi ve yapısı X-ışınları tek kristal kırınım tekniği ile aydınlatıldı. Komplekslerin termik özellikleri, eşzamanlı TG ve DTA teknikleri ile incelendi. Yapısında kristal suyu ve koordine su bulunan komplekslerin ilk bozunma aşamasında dehidrasyon veya deakuasyon meydana geldiği görüldü. Sonraki aşamada ise nötral ligandların uzaklaşması ve bsa ligantlarının bozunması gerçekleşmektedir. Son bozunma ürünü olarak karşılık gelen metal oksitler oluşmaktadır. Anahtar Kelimeler: benzensülfonat, imidazol, 1,10-fenantrolin, 2,2'-bipridin, etilendiamin, termik analiz, kompleks.

In this work mixed ligand complexes of benzenesufonates with Mn(II), Co(II), Ni(II) and Cu(II) transition metal ions with imidazole (im), 1,10-phenanthroline (phen) 2,2'-bipyridine (bpy), ethylenediamine (en) and aqua ligands and [Mn(bsa)2(bpy)2]·H2O complex, in which benzenesulfonic acid (bsa) acts as ligand, are synthesized. The structural and spectroscopic properties of synthesized complexes were investigated by elemental analysis, magnetic susceptibility, conductivity measurements together with infra-red and ultra-violet visible techniques. Thermal behaviours of the complexes were simultaneously determined by thermal analysis techniques (TG and DTA). The crystal structure of [Mn(bsa)2(bpy)2]·H2O complex has also been studied to understand bonding of the ligands in this complex. Its structure was identified by X-ray single crystal diffraction technique. The thermal behaviours of these complexes were investigated by means of TG, DTA techniques. In the thermal analysis of the complexes containing lattice or ligand water, the first decomposition stage corresponds to the dehydration or deaquation. At the next stages the elimination of the neutral ligands and the decomposition of bsa ligands proceed. The final decomposition products were found to be the respective metal oxides. Keywords: benzenesulfonate, imidazole, 1,10-phenanthroline, 2,2'-bipyridine, ethylenediamine, thermal analysis, complex.
Synthesis, Spectroscopic and Thermal Properties of Some Aliphatic and Aromatic Benzenesulfonates
Tez (yüksek lisans) -- Ondokuz Mayıs Üniversitesi, 2007
Libra Kayıt No: 12666
Keywords: Kimya; Benzen Sülfonatlar; Etilendiamin; Fenantrolin; Chemistry; Kompleksler; Benzenesulfonates; İmidazoller; Ethylenediamine; Phenanthroline; Complexes; Imidazoles; TEZ YÜK LİS Y51b [2007]